Vitamin D and retinal microvascular damage: The Rotterdam Study. Issue 49 (December 2016) - Mutlu, Unal; Ikram, M Arfan; Hofman, Albert; de Jong, Paulus T V M; Uitterlinden, Andre G; Klaver, Caroline C W; Ikram, M Kamran
Abstract : Abstract: Vitamin D has been linked to various cardiovascular risk factors including indices of large-vessel disease. However, it remains unclear whether vitamin D is also associated with microvascular damage. In a community-dwelling population, we studied associations between vitamin D serum levels and retinal microvascular damage defined as retinopathy signs, narrower arterioles, and wider venules. From the population-based Rotterdam Study, we included 5675 participants (age ≥45 years) with vitamin D data and gradable retinal photographs. Serum levels of vitamin D were measured using an antibody-based assay. Retinal exudates, microaneurysms, cotton wool spots, and dot/blot hemorrhages were graded on fundus photographs by experienced graders in the whole sample; retinal vascular calibers, that is, arteriolar and venular diameters, were semiautomatically measured in a subsample (n = 2973). We examined the cross-sectional association between vitamin D and retinal microvascular damage using logistic and linear regression models, adjusting for age, sex, and cardiovascular risk factors. We found that persons with lower vitamin D levels were more likely to have retinopathy (adjusted odds ratio per standard deviation (SD) decrease of vitamin D = 1.30; 95% confidence interval (CI): = 1.12–1.49). Furthermore, lower vitamin D levels were associated with wider venular calibers (adjusted mean difference per SD decrease in vitamin D = 1.35; 95% CI = 0.64–2.06). This association was strongest among men ( P for interaction = 0.023). Lower levels of vitamin D are associated with retinal microvascular damage, suggesting that the link with cardiovascular risk may partly run through changes in the microvasculature.